The Effect of the Cooperative Learning Model of Student Team Achievement Division (STAD) and Learning Motivation on Student Learning Outcomes in the Citizenship Education Subject - Juli Herawati Padang; Sepriandison Saragih; Prini Desima Evawani Ambarita (STAI MA'ARIF MAGETAN, INDONESIA, 2026)
This study aims to determine the effect of the cooperative learning model of the Student Teams Achievement Division (STAD) type and learning motivation on student learning outcomes in Civics Education subject at grade X SMA Negeri 5 Pematangsiantar in the even semester of the 2025/2026 academic year. This study employed a quantitative approach with a descriptive correlational method. The population consisted of all grade X students totaling 360 people, with a sample of 72 students selected using purposive random sampling technique at 20% of the total population. Data were collected through a Likert scale questionnaire and direct observation. Data analysis was performed using multiple linear regression with the IBM SPSS Statistics 26 program. The results showed that: (1) the STAD cooperative learning model had a positive and significant effect on student learning outcomes with a t-value of 7.841 and a significance of 0.000; (2) learning motivation had a positive and significant effect on student learning outcomes with a t-value of 6.496 and a significance of 0.000; (3) the STAD learning model and learning motivation simultaneously had a significant effect on student learning outcomes with an F-value of 66.664 and a significance of 0.000. The coefficient of determination (R Square) of 0.659 indicates that both independent variables contributed 65.9% to the variation in student learning outcomes, while the remaining 34.1% was influenced by other factors outside this study.